FP-LAPW Study of Structural, Electronic, Elastic and Optical Properties of Alkali Hydrides Compounds XH (X= Li, Na, K, Rb, Cs) - Jaradat, Raed (An-Najah National University, 2018)
Based on the density functional theory, the full-potential linearized augmented plane wave (FP-LAPW) method has been carried out to determine the structural stability of different crystallographic phases, the pressure-induced phase transition, the electronic properties, the elastic constants and their related properties, the mechanical properties, the thermodynamic properties as well as the optical properties of LiH, NaH, KH, RbH and CsH compounds. The rocksalt (RS), zincblende (ZB), cesium chloride (CsCl) and wurtzite (WZ) structures are considered. The Perdew, Burke and Ernzerhof Generalized Gradient Approximation (PBE-GGA) approach was used for the exchange-correlation potential to compute the equilibrium structural parameters, transition pressure, elastic constants and their related properties, the mechanical properties as well as the thermodynamic properties. The PBE-GGA and modified Becke-Johnson (mBJ-GGA) schemes have been used for the exchange-correlation potential to calculate the band structures and optical properties. The alkali hydrides lattice constant increases as going from Li to Cs in the periodic table, while bulk modulus decreases. The calculated band structures using the mBJ-GGA approach have an insulating nature for these compounds in all the considered structures, except the LiH and CsH in CsCl structure, which show a semi-conducting behavior. The calculated elastic constants for alkali hydrides in the four structures RS, CsCl, ZB and WZ at ambient pressure are mechanically stable, except LiH and NaH in CsCl structure. The mBJ-GGA scheme is found to be more accurate than PBE-GGA in computing the energy-band gap and optical properties compared to the experimental results. The elastic constants (C11, C44, B) and their related properties in the RS structure are increasing with increasing pressure, C12 decreases as the pressure increases indicates that these compounds are unstable under high pressure, and the RS structure transforms to CsCl structure. Elastic constants, bulk modulus, Shear modulus (stiffness) and Debye temperatures of these compounds decrease as going from Li to Cs in the periodic table. These compounds in the RS structure are more mechanically stronger at ambient conditions. Alkali hydrides except the LiH and CsH in CsCl structure are suitable as dielectric compounds; they have a wide direct energy band gap. Alkali hydrides have a wide absorption region, on the other hand NaH and RbH absorption is very huge compared with LiH, KH and CsH absorption. NaH and RbH are excellent absorbent materials; maximum absorption regions are located in the middle ultraviolet (MUV) region and far ultraviolet (FUV) region. LiH, RbH and CsH compounds are also found to be a wide direct energy band gap; therefore, they could be suitable for the optoelectronic UV device applications. The absorption coefficient α(w), imaginary part of dielectric constant ε_2 (w) and the extinction coefficient k(w) for alkali compounds vary in the same way. The calculated ground state parameters for these compounds in each structure are well compared with the available theoretical and experimental results, and most of them are in good agreement with other calculations and experimental measurements.
Keywords: FP-LAPW Study of Structural, Electronic, Elastic and Optical Properties of Alkali Hydrides Compounds XH (X= Li, Na, K, Rb, Cs)